Dynamika i kierunki zmian rynku pracy na obszarach wiejskich - Wawrzonek, Anna (Wydawnictwo Naukowe UAM, 2013)
The main issue of this article is to present the refl ections concerning the directions and the dynamics of the labor market transformation in rural areas. The article also presents the supporting and motivating activities which are aimed to keep village inhabitants vocationally and professionally active. The article moreover outlines the changing image of Polish rural areas and the social perception and attitude to those changes. The author of this presentation pays particular attention to the employment policy towards rural areas, including the activities which are directed to create non-farms jobs. This is to be achieved by educational and advisory support and promotion of the idea of lifelong learning.
The Dynamics and Directions of Changes in the Jobs Market in Rural Areas
Keywords: employment policy; non-farms job; lifelong learning; vocationally and professionally